Effect of Maintenance Azithromycin on Established Bronchiolitis Obliterans Syndrome in Lung Transplant Patients - Nancy R Porhownik; Wael Batobara; Wayne Kepron; Helmut W Unruh; Zoheir Bshouty (Canadian Respiratory Journal)
BACKGROUND: Bronchiolitis obliterans syndrome (BOS), the main cause of late mortality following lung transplantation, is defined as an irreversible decline in forced expiratory volume in 1 s (FEV1).Previous studies using azithromycin for BOS in lung transplant patients have demonstrated a potential reversibility of the decline in FEV1.